Effect of EDTA on the growth and copper accumulation of sweet sorghum and sudangrass seedlings - Székely, Árpád (Acta Biologica Szegediensis, 2011)
The effect of EDTA on the growth parameters, copper accumulation and the translocation of Cu from root to shoot tissues was analyzed in sweet sorghum (Sorghum bicolor var. saccharatum (L.) Mohlenbr. Róna1 genotype) and sudangrass (Sorghum sudanense (Piper) Stapf cv. Akklimat). Although treatment with 200 μM EDTA enhanced the growth parameters and the translocation factor for Cu in both species, it did not increase the total accumulation of copper in plants grown in the presence of 10-6 M Cu2+ concentration.